1996
DOI: 10.1042/bj3200917
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between organic anions, micelles and vesicles in model bile systems

Abstract: Biliary lipid secretion probably involves both 'micellization' and 'vesiculization' of bile-canalicular membrane lipids. Several hydrophilic organic anions inhibit the secretion of lipids into the bile without altering bile salt secretion [Verkade, Vonk and Kuipers (1995) Hepatology 21, 1174-1189]. Hydrophobic organic anions do not interfere with biliary lipid secretion. We investigated whether the organic-anion-induced inhibition of biliary lipid secretion in vivo could be attributed to inhibition of micelliz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2000
2000
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…It is possible that ICG with its high LogP value (6.05 at pH 7.4; low water solubility) may bind to lipid and cause the liposome membrane to become sticky, thus forming liposome aggregations, detected by 90° light scattering and photon correlation spectroscopy as ICG induced an increase in the light scattering and apparent diameter (Figure ). Others have mixed ICG with preformed liposomes composed of various lipids and observed aggregation or fluorescence enhancement. , However, these studies did not probe concentration-dependent effects. In our studies, we evaluated and found nonlinear concentration effects and used the information for ICG–liposome admixtures related to ICG–lipid binding and fluorescence enhancement to fine-tune an optimal composition to construct ICG incorporated completely into liposome membranes.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is possible that ICG with its high LogP value (6.05 at pH 7.4; low water solubility) may bind to lipid and cause the liposome membrane to become sticky, thus forming liposome aggregations, detected by 90° light scattering and photon correlation spectroscopy as ICG induced an increase in the light scattering and apparent diameter (Figure ). Others have mixed ICG with preformed liposomes composed of various lipids and observed aggregation or fluorescence enhancement. , However, these studies did not probe concentration-dependent effects. In our studies, we evaluated and found nonlinear concentration effects and used the information for ICG–liposome admixtures related to ICG–lipid binding and fluorescence enhancement to fine-tune an optimal composition to construct ICG incorporated completely into liposome membranes.…”
Section: Discussionmentioning
confidence: 97%
“…It is possible that ICG with its high LogP value (6.05 at pH 7.4; low water solubility) 18 may bind to lipid and cause the liposome membrane to become sticky, thus forming liposome aggregations, detected by 90° light scattering and photon correlation spectroscopy as ICG induced an increase in the light scattering and apparent diameter (Figure 1 ). Others have mixed ICG with preformed liposomes composed of various lipids and observed aggregation 19 or fluorescence enhancement. 14 , 20 However, these studies did not probe concentration-dependent effects.…”
Section: Discussionmentioning
confidence: 99%
“…221 This conclusion has been supported by a number of in uitro studies, which have indicated the relative efficacy of micellar bile acids to extract lipids from isolated liver plasma, erythrocyte, or model membranes. 106,190,[222][223][224][225] Recent work by Cohen et alZ2' showed that bile acids showed selectivity toward the cesses. 173,174,181 years .…”
Section: Obscurities In the Process Of Biliarymentioning
confidence: 98%
“…Bile and duodenal cannulas were joined to maintain the enterohepatic circulation of biliary components.When BDT was subsequently infused in both animals, its excretion was strongly and negatively correlated to the lipid:bile acid ratio of bile (r=-0.97), supporting a dose dependent effect of canalicular BDT in uncoupling lipid excretion. Upon gel filtration chromatogragphy of bile, bilirubin co-eluted with bile salts and not with biliary phospholipids or cholesterol, implicating an intracanalicular association between hydrophilic anions and bile salts mediating the uncoupling effect[110].To assess whether organic anions, including BDT, exerted their uncoupling effects by interfering with biliary micellisation, Verkade et al[112] studied their effects in model bile systems. In a system comprising of taurocholate, phospholipid and cholesterol the addition of BDT (5mM) did not affect mean vesicle particle size, in contrast to that of other organic anions, Rose Bengal (hydrophobic) and sulphated taurolithocholate (hydrophilic).…”
mentioning
confidence: 99%